THE EMERGENT OF FEMINISM - H, SESHAGIRI; M, RAVICHAND (International Journal of Psychosocial Rehabilitation, 2019)
No creation in the world is without argument and movement. The society itself is the posterior. Even feminism is no exception. Feminist literature is a literary trend that has emerged with the idea that women should describe their experiences and feelings from a woman's perspective. Feminists allege that women are oppressed in the patriarchal system and that sexuality and fertility are patriarchal relationships. Feminist literature began with the aim of proving existence, intending to eradicate masculinity, protecting women's equal rights and freedoms in all spheres, and preventing women from falling prey to superstition. Feminism is a surge, a worldview, a social ideology. They are all feminists who can think on behalf of women! Feminism is a protest against patriarchy and not against men. It has been prominent in some of the arguments that have emerged in the journey to confront discrimination that has become problematic. Feminists freely express their feelings, their language style. No matter how many poetic movements came in literature, women were not taken into consideration. When 1975 - 85 was declared the "International Decade of Women" by the United Nations. In the West, especially in the United States, the woman Liberation Struggle (Women's Lib) began.